Biomateriais: deposição de hidroxiapatita sobre superfície de Ti-cp modificada por aspersão térmica - Almeida Filho, Edson de [UNESP]; Assis, Camila Molena de [UNESP]; Vercik, Luci de Oliveira [UNESP]; Guastaldi, Antonio Carlos [UNESP] (Sociedade Brasileira de Química, 2007)
The osseointegrated titanium implants are reliable and safe alternatives to treatments for long periods of time. For surface modification, thermal aspersion of TiO2 was used. The samples with and without TiO2 were treated with NaOH and SBF in order to obtain a layer of HA. Characterization was done by SEM and FTIR. The images of HA obtained by SEM show a uniform morphology and a porous structure with spherical particles. The IR spectra show that the surface of Ticp/ TiO2 is more favorable for the HA deposit, as can be seen by the increase of the crystalline structure and the very intense and defined bands of the OH group of HA that is verified about 3571 and 630 cm-1. Thus the Ticp/ TiO2 surface presents a satisfactory nucleation of HA when compared to Ticp.
Biomaterials: deposition of hydroxyapatite on Ticp surfaces modified by thermal aspersion
Keywords: hydroxyapatite; surface modification; biomimetic